2009
DOI: 10.1007/s10669-009-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide standards on exposure to electromagnetic fields: an overview

Abstract: Over the last years, a wide debate has developed on the possible health effects of exposure to electromagnetic fields. In-depth research activity was therefore developed by the international scientific community aimed at evaluating the risk associated with exposure to this type of radiation. At the same time, various international institutions began to issue recommendations on exposure limits valid for workers and for the population in the frequency range up to 300 GHz. Most of the recently revised safety stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…At the moment, the most important concern is the contradictory information about mobile telephony base station antennas and their declared effects on human health [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the most important concern is the contradictory information about mobile telephony base station antennas and their declared effects on human health [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…For those who are interested in the standards on exposure to electromagnetic fields, I would recommend the papers of Markov (2000) and Grandolfo (2009). While the first paper relates to measurements in radiofrequency range, the paper of Grandolfo reviews the worldwide standards and guidelines.…”
Section: Chernobyl and Fukushimamentioning
confidence: 99%
“…The ELF-EMF potential effects on organisms have become a subject to many extensive studies (Furse et al 2008;Grandolfo 2009;Waite et al 2011). Although the data from these studies have shown different results, the World Health Organization (WHO) recommends that environmental ELF-EMFs are harmless to human health.…”
Section: Introductionmentioning
confidence: 99%